Implementation Of Pancasila Student Profile By Citizens Education Teachers As An Effort To Realize Nation Character - Jamilah Jamilah; Ade Suherman; Prima Melati; Arik Darojat; Hermansyah Hermansyah; Nenden Rosita (Indonesian Journal of Community Empowerment (IJCE), 2021)
ABSTRACTOne of the challenges for the world of education today is how to develop character education for students. Kemendikbudristek set 6 indicators from the Pancasila Student Profile. In order to facilitate the internalization of the Pancasila Student Profile in learning by both teachers and students, the Merdeka Mengajar Platform (PMM) was developed. Character education can be interpreted with value education, character education, moral education, character education. In other words, character education is an essential part of the educational process, interpreted as a system of inculcating character values ​​to school members which includes components of knowledge, awareness or willingness and action to implement these values, both towards God Almighty, oneself, and others. others, the environment, and nationality so that they become human beings. Likewise, an educator is said to have character if he has values ​​and beliefs that are based on the nature and purpose of education and is used as a moral strength in carrying out his duties as an educator. This service aims to improve the competence of Civics teachers in applying the profile of Pancasila students as an effort to realize the nation's character. The subjects of the service are Civics Education teachers, especially those in Malangbong District, Garut Regency through Webinar and Workshop activities. The results obtained from these activities are that teachers are motivated in understanding and developing the application of Pancasila student profiles as an effort to realize the nation's character in their respective schools. Salah satu tantangan bagi dunia pendidikan saat ini adalah bagaimana mengembangkan pendidikan karakter bagi siswa. Kemendikbudristek menetapkan 6 indikator dari Profil Pelajar Pancasila. Guna mempermudah internalisasi Profil Pelajar Pancasila dalam pembelajaran baik oleh guru maupun siswa, dikembangkan Platform Merdeka Mengajar (PMM). Pendidikan karakter dapat dimaknai dengan pendidikan nilai, pendidikan budi pekerti, pendidikan moral, pendidikan watak. Dengan kata lain pendidikan karakter merupakan bagian esensial dalam proses pendidikan, dimaknai sebagai sistem penanaman nilai-nilai karakter kepada warga sekolah yang meliputi komponen pengetahuan, kesadaran atau kemauan dan tindakan untuk melaksanakan nilai-nilai tersebut, baik terhadap Tuhan Yang Maha Esa, diri sendiri, sesama, lingkungan, maupun kebangsaan sehingga menjadi insan kamil. Demikian juga, seorang pendidik dikatakan berkarakter jika ia memiliki nilai dan keyakinan yang dilandasi hakikat dan tujuan pendidikan serta digunakan sebagai kekuatan moral dalam menjalakan tugasnya sebagai pendidik. Pengabdian ini bertujuan untuk meningkatkan kompetensi guru PKn dalam menerapkan profil pelajar pancasila sebagai upaya mewujudkan karakter bangsa. Subjek pengabdian adalah guru-guru PKn khususnya yang berada di Kecamatan Malangbong Kabupaten Garut melalui kegiatan Webinar dan Workshop. Hasil yang diperoleh dari kegiatan tersebut yaitu termotivasi nya guru dalam memahami dan mengembangkan menerapkan profil pelajar pancasila sebagai upaya mewujudkan karakter bangsa di sekolah masing-masing.